Pelatihan Metode Pengajaran Bahasa Inggris Communicative Bagi Guru TK Ar-Rahman, Konawe Sulawesi Tenggara - Rahmiatin, Titin; Zur, Sarjaniah (Amaliah: Jurnal Pengabdian Masyarakat, 2017)
The aims of HPM (community service grant) is to help pre school teachers of TK Arrahman of Tirawuta village of Konawe Regency in understanding the techniques in communicative English teaching for young learners. The methods used to achieve the goals was through all day workshop in which it focused on giving theories and making simulation as well. The result of the program was that the participants are able to understand the characteristics of young learners, conceive appropriate methods for teaching English to young learners, and practice the method into a microteaching activity. This kind of community service grant is fully granted by the Unit of Community Service of Muhammadiyah University of Kendari.